2022
DOI: 10.7150/ijms.68394
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of nasopharyngeal carcinoma patients with T1-2 stage in intensity-modulated radiotherapy era

Abstract: Objectives: To evaluate long-term outcomes and late toxicities of nasopharyngeal carcinoma (NPC) patients with T1-2N0-3M0 stage in intensity-modulated radiotherapy (IMRT) era. Materials and Methods: From June 2005 to October 2013, 276 patients confirmed T1-2N0-3M0 NPC treated with IMRT were reviewed, with 143 (51.8%) N0-1 disease and 133 (48.2%) N2-3 disease. Among them, 76.4% received chemotherapy. The prescribed doses given to the primary tumor and lymph nodes were 66Gy in 30 fractions. Results: After a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…In recent years, the immunotherapy dominated by PD-1/PD-L1 immune checkpoint inhibitors has been gradually applied to the comprehensive treatment regimen for various types of tumors. Camrelizumab is the third PD-1 drug made in China after toripalimab and sintilimab and can activate T cells by blocking PD-1/PD-L1 binding, thereby weakening the immunosuppression within the patients' organism and enhancing the tumor-killing effect [ 7 , 8 ]. Zhou et al gave the patients with advanced nasopharyngeal carcinoma targeted therapy combined with immunotherapy (anrotinib + camrelizumab), and the patients' recheck showed that they had shrunken lesions, significantly relieved cough and active shortness of breath, and remarkably improved quality of life [ 9 ], suggesting that anrotinib + camrelizumab has treatment effect on the patients with nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the immunotherapy dominated by PD-1/PD-L1 immune checkpoint inhibitors has been gradually applied to the comprehensive treatment regimen for various types of tumors. Camrelizumab is the third PD-1 drug made in China after toripalimab and sintilimab and can activate T cells by blocking PD-1/PD-L1 binding, thereby weakening the immunosuppression within the patients' organism and enhancing the tumor-killing effect [ 7 , 8 ]. Zhou et al gave the patients with advanced nasopharyngeal carcinoma targeted therapy combined with immunotherapy (anrotinib + camrelizumab), and the patients' recheck showed that they had shrunken lesions, significantly relieved cough and active shortness of breath, and remarkably improved quality of life [ 9 ], suggesting that anrotinib + camrelizumab has treatment effect on the patients with nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The article comes to the conclusion that SC-VMAT with three full arcs was inferior in dosimetry to DC-VMAT with a single arc (15) . Colli-VMAT plans with smaller angular sections (16) have comparable target coverage and spare healthy tissues in comparison to Std-VMAT https://www.indjst.org/ plans (17) , according to analysis by Beom Seok Ahn et al In the same (16) , a precise substantial decrease in total MUs was also noted.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of radiation encephalopathy after radiotherapy for NPC is lower than that in conventional radiotherapy because of the use of IMRT technology 7 , 8 . However, functional MRI studies on NPC after IMRT have showed that the brain volume for patients without radiation encephalopathy have decreased compared to those of healthy persons, suggesting that although IMRT reduces the radiation dose in normal brain tissue, the effect of radiotherapy on brain tissue still exists 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%